SMG-1 and mTORC1 act antagonistically to regulate response to injury and growth in planarians - Gonzalez-Estevez, Christina; Felix, Daniel A.; Smith, Matthew D.; Paps, Jordi; Morley, Simon J.; James, Victoria; Sharp, Tyson V.; Aboobaker, A. Aziz (Public Library of Science, 2012)
Planarian flatworms are able to both regenerate their whole bodies and continuously adapt their size to nutrient status. Tight control of stem cell proliferation and differentiation during these processes is the key feature of planarian biology. Here we show that the planarian homolog of the phosphoinositide 3-kinase-related kinase (PIKK) family member SMG-1 and mTOR complex 1 components are required for this tight control. Loss of smg-1 results in a hyper-responsiveness to injury and growth and the formation of regenerative blastemas that remain undifferentiated and that lead to lethal ectopic outgrowths. Invasive stem cell hyper-proliferation, hyperplasia, hypertrophy, and differentiation defects are hallmarks of this uncontrolled growth. These data imply a previously unappreciated and novel physiological function for this PIKK family member. In contrast we found that planarian members of the mTOR complex 1, tor and raptor, are required for the initial response to injury and blastema formation. Double smg-1 RNAi experiments with tor or raptor show that abnormal growth requires mTOR signalling. We also found that the macrolide rapamycin, a natural compound inhibitor of mTORC1, is able to increase the survival rate of smg-1 RNAi animals by decreasing cell proliferation. Our findings support a model where Smg-1 acts as a novel regulator of both the response to injury and growth control mechanisms. Our data suggest the possibility that this may be by suppressing mTOR signalling. Characterisation of both the planarian mTORC1 signalling components and another PIKK family member as key regulators of regeneration and growth will influence future work on regeneration, growth control, and the development of anti-cancer therapies that target mTOR signalling.